2015
DOI: 10.1002/erv.2347
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Between Lifetime Eating Problems and Mood and Anxiety Disorders: Results from the Canadian Community Health Survey of Mental Health and Well‐being

Abstract: This study was to examine profiles of eating problems (EPs), mood and anxiety disorders and their comorbidities; explore risk patterns for these disorders; and document differences in health service utilization in a national population. Data were from the Canadian Community Health Survey of Mental Health and Well-being. The lifetime prevalence of EPs was 1.70% among Canadians, compared with 13.25% for mood disorder, 11.27% for anxiety disorder and 20.16% for any mood or anxiety disorder. Almost half of those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…A recent study in Australia by Swinbourne et al [2] found that 65% of the EDs patients also met criteria for at least one comorbid anxiety disorder Of the anxiety disorders diagnosed, social phobia was most frequently diagnosed (42%) followed by post-traumatic stress disorder (26%), generalised anxiety disorder (23%), obsessive-compulsive disorder (5%), panic/agoraphobia (3%) and specific phobia (2%). Similar high rates of comorbidity have also been reported by other authors [3,4]. It is interesting that more that two thirds of the patient report that the onset of the anxiety disorder to precedes the onset of the ED [2].…”
Section: Comorbiditysupporting
confidence: 86%
“…A recent study in Australia by Swinbourne et al [2] found that 65% of the EDs patients also met criteria for at least one comorbid anxiety disorder Of the anxiety disorders diagnosed, social phobia was most frequently diagnosed (42%) followed by post-traumatic stress disorder (26%), generalised anxiety disorder (23%), obsessive-compulsive disorder (5%), panic/agoraphobia (3%) and specific phobia (2%). Similar high rates of comorbidity have also been reported by other authors [3,4]. It is interesting that more that two thirds of the patient report that the onset of the anxiety disorder to precedes the onset of the ED [2].…”
Section: Comorbiditysupporting
confidence: 86%
“…In a Canadian study almost half of all patients with eating problems were also found to have mood or anxiety disorders 31. Similarly, in a Swedish study half of patients with eating disorders had depression and one-quarter endorsed substance abuse 32.…”
Section: Common Comorbiditiesmentioning
confidence: 91%
“…(13) Further, when considering help-seeking populations, the prevalence of DE in patients with mental illness were in the range of 4.1%-43%. (14,15) One study suggested that girls presenting with depressive and anxiety disorders demonstrated behaviours within subclinical anorexia (restrictive eating), which were associated with higher levels of weight concerns. (5) BID among patients diagnosed with schizophrenia spectrum disorders underlie negative cognitions concerning body image, such as dullness in movement, powerlessness, lifelessness and fragility.…”
Section: Introductionmentioning
confidence: 99%